P04 A dose effect of the disease risk gene HLA DR3 contributes to numerical and functional impairment of CD4+CD25+ regulatory T cells in patients with autoimmune hepatitis. (6th September 2011) - Wang, P; Underhill, J; Longhi, M S; Mieli-Vergani, G; Ma, Y; Vergani, D
Abstract : Introduction: Autoimmune diseases are frequent among first degree relatives (FDR) of patients with autoimmune hepatitis (AIH), but concordance for AIH is rare. A numerical and functional impairment of CD4 pos CD25 pos regulatory T cells (Tregs) is described in AIH patients, but no study has addressed Treg status in their FDR. Aim: To define whether the defect of Tregs in AIH is inherited and is associated with disease predisposing HLA genes. Method: 44 children with AIH (33 AIH-1 and 11 AIH-2, median age 13.5 yrs, 23 females), 65 FDR from 34 families [23 fathers, 47 yrs (38–58); 28 mothers, 44 yrs (24–53) and 14 siblings, 7 females, 13 yrs (5–24)] and 42 healthy subjects [HS, 36 yrs (22–54), 37 females] were studied. Tregs were purified from PBMCs using immunomagnetic beads and their phenotype and frequency was assessed by flowcytometry. CD25 neg cells were used as responders in co-culture with Tregs and their proliferation was measured by 3 H-thymidine incorporation. HLA genotyping was performed by PCR using gene specific primers. Results: The frequency of the disease predisposing gene HLA DR3 was significantly higher in patients (71%) and their FDR (56%) than in HS (23%, p<0.0001 and p<0.005). The frequency of homozygous DR3 was higher in patients (29%) than in FDR (9%, p=0.015) and HS (0%, p=0.001). In patients the frequency of HLA A1-B8-DR3 haplotype (42%) was higher than in FDR (27%, p=0.15) and HS (16%, p=0.02). The frequency of conventional CD4 pos CD25 pos Tregs was lower in patients (6.2%±0.5) than in FDR (9.3%±0.7, p=0.0016) and HS (9.7%±0.8, p=0.001). Though the frequency of CD4 pos CD25 high CD127 neg 'True' Tregs was similar among patients, FDR and HS (6.0%±0.6, 6.3%±0.4 and 6.2%±0.5), their suppressive function was lower in patients (13.6% reduction of CD25 neg cell proliferation) than in FDR (28.8%, p=0.007) and HS (36.9%, p<0.0001). Among subjects positive for HLA DR3, the frequency of conventional Tregs was lower in patients (5.6%±0.5) than in FDR (8.4%±0.97, p=0.01) and in HS (9.1%±1.4, p=0.006). Among subjects positive for HLA A1-B8-DR3 haplotype, the frequency of Tregs was lower in patients (6.0%±0.7) than in FDR (9.1%±1.5, p=0.045) and HS (9.8%±1.8, p=0.02). Conclusion: A numerical and functional impairment of Tregs in AIH patients is associated with possession of HLA disease predisposing genes, and in particular HLA DR3 homozygosity. Possession of DR3 was not associated to a similar immune regulatory impairment in FDR and HS, suggesting that a gene dose effect contributes to the impairment of immunoregulation and to the development of AIH.